2004
DOI: 10.1161/01.cir.0000121730.41801.12
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Translocase/CD36 Deficiency Does Not Energetically or Functionally Compromise Hearts Before or After Ischemia

Abstract: Background-Evidence from humans suggests that fatty acid translocase (FAT)/CD36 deficiency can lead to functionally and/or energetically compromised hearts, but the data are equivocal, and the subject remains controversial. In this report we assessed the contribution of FAT/CD36 to overall fatty acid oxidation rates in the intact heart and determined the effect of FAT/CD36 on energy metabolism during reperfusion of ischemic hearts. Methods and Results-Isolated working hearts from wild-type and FAT/CD36-knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 32 publications
5
100
1
Order By: Relevance
“…This confirmed our studies with the radio labeled tracers 125 I-BMIPP (a non-metabolizable fatty acid analog), 125 I-IPPA (a metabolizable fatty acid analog) and 8-fluorodeoxyglucose (a glucose analog), which were initiated because of the observation that CD36 KO mice have fasting hypoglycemia (Coburn, Knapp, Febbraio, Beets, Silverstein, & Abumrad, 2000). Under normal and high fat conditions, we found that the CD36 KO mouse heart is entirely compensated in terms of ATP and acylCoA fatty acids by utilization of glucose (Kuang, Febbraio, Wagg, Lopaschuk, & Dyck, 2004). Even at high work loads, CD36 KO mouse hearts performed as well, if not better than wild type hearts because of full compensation for energy by glucose.…”
Section: Other Functions Of Cd36 That May Impact Cardiovascular Diseasementioning
confidence: 98%
See 3 more Smart Citations
“…This confirmed our studies with the radio labeled tracers 125 I-BMIPP (a non-metabolizable fatty acid analog), 125 I-IPPA (a metabolizable fatty acid analog) and 8-fluorodeoxyglucose (a glucose analog), which were initiated because of the observation that CD36 KO mice have fasting hypoglycemia (Coburn, Knapp, Febbraio, Beets, Silverstein, & Abumrad, 2000). Under normal and high fat conditions, we found that the CD36 KO mouse heart is entirely compensated in terms of ATP and acylCoA fatty acids by utilization of glucose (Kuang, Febbraio, Wagg, Lopaschuk, & Dyck, 2004). Even at high work loads, CD36 KO mouse hearts performed as well, if not better than wild type hearts because of full compensation for energy by glucose.…”
Section: Other Functions Of Cd36 That May Impact Cardiovascular Diseasementioning
confidence: 98%
“…Whatever the mechanism, absence of CD36 affects fatty acid uptake by various tissues, including adipocytes and muscle, and this leads to measurable phenotype (Febbraio, et al, 1999). CD36 KO mice have a fasting hypoglycemia and different energy substrate use in heart (Kuang, Febbraio, Wagg, Lopaschuk, & Dyck, 2004). Uptake of fatty acid analogs was specifically reduced in muscle and adipocytes of mice, and has been shown to be reduced in heart of CD36-deficient humans (Coburn, Knapp, Febbraio, Beets, Silverstein, & Abumrad, 2000,Watanabe, et al, 1998,Hwang, et al, 1998,Tanaka, et al 2001).…”
Section: Cd36 Structure and Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the sarcolemmal membrane of the working heart, fatty acid translocase (FAT/CD36) has been shown to account for as much as 50% of the fatty acid acid taken up into the cell and subsequently used for oxidation. 14 A key site of control for the transport of fatty acids into the mitochondria is the enzyme carnitine palmitoyl transferase 1 (CPT-1), which is located on the outer mitochondrial membrane. This enzyme is inhibited by malonyl-CoA, the levels of which are indirectly regulated by AMPK.…”
Section: Introductionmentioning
confidence: 99%